1967
DOI: 10.1073/pnas.58.5.2028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bacteriophage infection on the sulfur-labeling of sRNA.

Abstract: Several examples of viral-induced modifications of cellular ribonucleic acids have been reported. After infection of Escherichia coli with T-even bacteriophage, Sueoka and Kano-Sueokal 2 found quantitative as well as qualitative changes in leucyl-tRNA's when compared to uninfected cells by chromatography on methylated albumin-kieselguhr (.IMAE). ]More recently, Waters and Novelli,3 using reverse phase chromatography, were able to confirm the early changes in leucyltRNA after T2 infection of E. coli and, in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

1968
1968
1977
1977

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The studies of cysteinedependent thiolation of tRNA (163) provided another tool for testing tRNA after phage infection. In uninfected and phage-infected cells grown on IS-sodium sulfate, all sulfur-containing RNA proved to be 4S RNA, the elution profiles of which on MAK columns were different for tRNA from infected and uninfected cells (163). The material of the major new peak from infected cells does not hybridize with E. coli DNA, but it hybridizes with T4 DNA; T4 mRNA and E. coli tRNA do not compete in this reaction (407).…”
Section: Virus Infection and Trnamentioning
confidence: 97%
“…The studies of cysteinedependent thiolation of tRNA (163) provided another tool for testing tRNA after phage infection. In uninfected and phage-infected cells grown on IS-sodium sulfate, all sulfur-containing RNA proved to be 4S RNA, the elution profiles of which on MAK columns were different for tRNA from infected and uninfected cells (163). The material of the major new peak from infected cells does not hybridize with E. coli DNA, but it hybridizes with T4 DNA; T4 mRNA and E. coli tRNA do not compete in this reaction (407).…”
Section: Virus Infection and Trnamentioning
confidence: 97%
“…20 ' rpm in a Spinco rotor SW-39. 10 20 30 Tube number that the T4 P32-sRNA (cpm) and E. coli sRNA (OD) have identical sedimentation profiles and consequently the same sedimentation constants, when centrifuged in a linear sucrose gradient.…”
mentioning
confidence: 99%
“…Modifications in transfer RNA (tRNA) chromatographic patterns after virus infection have been described by several laboratories.1-5 In a recent communication, we described distinct alterations in the chromatographic behavior of pulselabeled S35-tRNA after infection of Escherichia coli B with T-even bacteriophage. 6 The experimental data suggested that the observed S35 transition from the "normal" to the "infected" tRNA profile was virus-induced and that these changes were not the result of host tRNA modifications. The "infected" and "uninfected" sulfur-labeled profiles of tRNA as observed by chromatography on methylated albumin kieselguhr (iVIAK) are shown in Figure 1 where we have arbitrarily designated the radioactive regions as peaks 1, 2, and 3.…”
mentioning
confidence: 95%